Phosphorylated Forms of STAT1, STAT3 and STAT5 Are Expressed in Proliferating but Not Involuted Infantile Hemangioma - Sulzberger, Lucy; Tan, Elysia M. S.; Davis, Paul F.; Brasch, Helen D.; Tan, Swee T.; Itinteang, Tinte (Frontiers in Surgery, 2018)
We have recently demonstrated the expression of embryonic stem cell markers on the endothelium of infantile hemangioma, a functional hemogenic endothelium with the capacity for primitive erythropoiesis in vitro. Despite recent work characterizing stem cells within proliferating infantile hemangioma, the expression of STAT proteins, well documented for their roles in stem cell signaling, has not been investigated. 3,3-Diaminobenzidine and immunofluorescent immunochemical staining revealed expression of pSTAT1, pSTAT3 and pSTAT5 in proliferating infantile hemangioma samples with the strongest expression of pSTAT3. There was reduced expression of these pSTAT proteins in the involuted infantile hemangioma samples. Western blotting confirmed the identification of all these three proteins in proliferating infantile hemangioma. It is therefore not surprising that the phosphorylated/activated forms of these proteins are relatively abundantly expressed in proliferating, in comparison to, involuted infantile hemangioma samples. We speculate that the reduced STAT activation as infantile hemangioma involutes, is a reflection of the depletion of the abundant stem cells within proliferating infantile hemangioma, as the lesion involutes.